KARAKTERISTIK AKAD PEMBIAYAAN AL-QARDH SEBAGAI AKAD TABARRU’ - Farid Budiman (Yuridika, 2013)
Basically, the contract tabarru’ is give (giving something) or lend (lending something). If the ‘akad’ is lent something, the object can be money lending (lending) or service (lending yourself). Though the parties do good must not profit from the transaction tabarru’, he still could ask the other party receives a kindness to reimburse -costs incurred for the transaction tabarru ‘is, but he still should not be taking advantage although a small amount of the transaction tabarru’.Keywords: akad, qardh, tabarru’.